2006
DOI: 10.3177/jnsv.52.307
|View full text |Cite|
|
Sign up to set email alerts
|

Beneficial Effect of Pretreatment and Treatment Continuation with Risedronate and Vitamin K<sub>2</sub> on Cancellous Bone Loss after Ovariectomy in Rats: A Bone Histomorphometry Study

Abstract: The following articles have been retracted by the Editorial Board of Journal of Nutritional Science and Vitaminology, because some parts of their contents were published in other journals. 1. Iwamoto J, Yeh JK, Takeda T, Sato Y. Comparative effects of vitamin K and vitamin D supplementation on calcium balance in young rats fed normal or low calcium diets. J Nutr Sci Vitaminol 51, 211-215, 2005 2. Iwamoto J, Seki A, Takeda T, Sato Y, Yamada H, Yeh JK. Effect of risedronate on the cortical and cancellous bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Effect of combined use of vitamin K2 and bisphosphonate on osteoporosis was evaluated in rat models. It was recommended that vitamin K2 could ameliorate the suppressive effect of bisphosphonates on bone turnover and increase the bone volume as well as the bone formation parameters [ 68 , 74 ]. Other reviews emphasized the potentially positive effect of combined treatment with bisphosphonate and vitamin K2 for preventing the fractures in postmenopausal osteoporotic women [ 75 , 76 ].…”
Section: Effects Of Vitamin K On Different Osteoporotic Rat Modelsmentioning
confidence: 99%
“…Effect of combined use of vitamin K2 and bisphosphonate on osteoporosis was evaluated in rat models. It was recommended that vitamin K2 could ameliorate the suppressive effect of bisphosphonates on bone turnover and increase the bone volume as well as the bone formation parameters [ 68 , 74 ]. Other reviews emphasized the potentially positive effect of combined treatment with bisphosphonate and vitamin K2 for preventing the fractures in postmenopausal osteoporotic women [ 75 , 76 ].…”
Section: Effects Of Vitamin K On Different Osteoporotic Rat Modelsmentioning
confidence: 99%
“…Among bisphosphonates (risedronate, alendronate, pamidronate, etidronate) risedronate (RIS) shows a higher antiresorptive effect 3,7,18,34) . It affects bone remodeling and increase bone mass through the inhibition of osteoclasts 23,24) . Its effect on osteoblasts, and the balance between osteoblastic and osteoclastic activity on bone turnover and healing, is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the animal studies, a much higher dosage of 30–50 mg MK-4/kg/day has been used, thus resulting in a significantly higher mineral content in cortical bone without bisphosphonate [ 31 ]. However, the results are inconsistent among different animals or strains [ 16 18 , 32 34 ]. In the present study, we did not observe significant increase in BMD or BMC at the lower level of ~100 μg/kg/day unless MK-4 was followed by risedronate.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of such prevention as well as the lack of other beneficial effects found in K to R cortex, such as the higher/larger BMD, BMC, and thickness, would explain why no significant effect was detectable in K to WO by the three-point bending test. In the MK-4 treated pre-OVX rats, Iwamoto et al reported the elevated eroded surface as well as the bone formation rate that remained high after the MK-4 withdrawal [ 16 ]. The cellular mechanisms of the elevated collagen degradation therefore have to be confirmed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation